Identification of polymorphisms in the 5 '-untranslated region of the TAFI gene: relationship with plasma TAFI levels and risk of venous thrombosis - Franco, R. F. (2001)
Background and Objectives. Thrombin activatable fibrinolysis inhibitor (TAFI) plays an important role in hemostasis, functioning as a potent fibrinolysis inhibitor. TAFI gene variations may contribute to plasma TAFI levels and thrombotic risk.Design and Methods. We sequenced a 2083-bp region of the 5 ' -regulatory region of the TAFI gene in 127 healthy subjects searching for variations, and correlated identified polymorphisms with plasma TAFI levels. TAFI polymorphisms were examined as risk factors for venous thrombosis by determining their prevalence in 388 patients with deep venous thrombosis (DVT) and in 388 controls.Results. Seven novel polymorphisms were identified: -152 A/G, -438 A/G, -530 C/T, -1053 T/C, -1102 T/G, -1690 G/A, and -1925 T/C. -152 A/G, -530 C/T and -1925 T/C were found to be in strong linkage disequilibrium, as were the -438 A/G, -1053 T/C, -1102 T/G and -1690 G/A, Plasma TAFI levels were higher in -43866/-1053CC/-1102GG/-1690AA homozygotes than In -438AG/-1053TC/-1102TG/-1690GA heterozygotes, and -438AA/-1053TT/-1102TT/-1690GG homozygotes had the lowest TAFI levels (p=0.0003). TAFI concentrations in -152AA/-530CC/-1925TT homozygotes were somewhat higher but not significantly different from levels observed for -152AG/-530CT/-1925TC heterozygotes, Taken in combination, -438AG/-1053TC/-1102TG/-1690GA and -438AA/-1053TT/-1102TT/-1690GG yielded an OR for DVT of 0.8 (95%CI: 0.6-1). in subjects aged < 35 years the OR was 0.7 (95%CI: 0.5-1.1), The OR for -152AG/-530CT/-1925TC was 1 (95%CI: 0.5-2.2) in the whole group of patients and controls, whereas in subjects aged <35 years the OR was 0.1 (95%CI: 0.02-0.9).Interpretation and Conclusions. Polymorphisms in the TAFI promoter determine plasma antigen levels and may influence the risk of venous thrombophilia. <(c)>2001, Ferrata Storti Foundation.